Transmisi Qira’at dalam Manuskrip Al-Qur’an Sinjai - Hana Maulydiah; Romlah Widayati; Salma Kamilah Putri (SUHUF, 2026)
This study examines the application of qira’at in an ancient Qur’anic manuscript from Sinjai, with particular emphasis on the principles of qira’at from the perspective of tariq asy-Syatibiyyah. The object of this research is the ancient manuscript of Syaikh Abdul Majid, focusing specifically on the qira’at annotations found on the manuscript margins. This study aims to analyze the patterns of qira’at application and to assess the consistency of the qira’at transmissions represented in the manuscript. The research is motivated by the limited number of studies on ancient Qur’anic manuscripts in the Nusantara that place the science of qira’at as the primary focus of academic inquiry. Therefore, this study is expected to contribute to and enrich the scholarly discourse on ancient Qur’anic manuscripts from the perspective of Qur’anic sciences. This research employs a qualitative method with a library research approach. The primary sources consist of the Sinjai ancient Qur’anic manuscript and the commentaries (syuruh) on the qira’at works of Imam asy-Syatibiy (w. 1388 M). The findings in the aspect of qira’at indicate that in juz 30 of the Mushaf of Syaikh Abdul Majid, there are 46 words in the manuscript margins that contain ikhtilaf al-qira’at, including differences related to both usuliyyah rules and farsy al-huruf. The qira’at presented in the margins of the Mushaf consistently follow al-qira’at as-sab‘. Although the presentation of qira’at in the margins is relatively concise, this is due to the fact that only a portion of the possible qira’at variations is displayed.